Faktor Penyebab dan Upaya Mengatasi Area Titik Buta pada Truk - Muhammad Ilhamdi Rusydi; Yoan Winata; Dhiny Yurichy Putri; Muhammad Fikri (Institut Transportasi dan Logistik Trisakti, 2021)
Truck drivers cannot see the entire area around the vehicle. This area that cannot be seen is called a blind spot. This article aims to analyze the factors causing blind spot areas on trucks and discuss the efforts that have been made to address the blind spots on trucks. The writing method used is a literature study of the research that has been done. The keywords used in the reference search include blind spot, driver and anthropometry. The search results show that the blind spot area is on each side of the truck, either caused by the vehicle design or the driver's anthropometry. Various attempts have been made to address blind spot areas, such as the use of mirrors, cameras and sensors. In addition, expanding the driver's vision area from inside the cabin can also be a solution. Based on the results of the literature study, it is concluded that the blind spot area is influenced by vehicle design and driver anthropometry